Afferent lymph veiled cells prime CD4+ T cell responses in vivo - McKeever, Declan J.; Awino, J.; Morrison, W. Ivan (Wiley, 1992)
The interdigitating cell (IDC) population of the lymph node paracortex is believed to be responsible for the induction of CD4+ T cell responses to soluble antigens. We have examined the role of afferent lymph veiled cells (ALVC), the putative precursors of IDC, in the induction of primary bovine CD4+ T cell responses in vivo. ALVC prepared from lymph draining an antigen inoculation site stimulated maximal responses in antigen‐specific T cell clones as soon as 30 min after inoculation. In addition, antigen‐pulsed ALVC were shown to induce primary antigen‐specific T cell responses when administered in vivo. Observed influences of fixation and the addition of chloroquine or class II major histocompatibility complex‐specific monoclonal antibodies on presenting function confirmed that ALVC process and present antigens using the endosomal pathway. We conclude that ALVC rapidly internalize antigens deposited in the periphery, and process them for presentation to naive T cells in the draining lymph node. Their function is, therefore, likely to be an important factor in the induction of primary T cell responses to soluble antigens in vivo.